Treatment of Potted Zebra Plant and Inch Plant with Antigibberellin Plant Growth Regulators Slows Stem Elongation in an Interior Green Wall - Lane W. Wiens; Kimberly A. Williams (HortTechnology, 2023)
In commercial interior green walls, plant trimming and replacement necessitated by stem elongation under low interior light levels is labor intensive and costly. Antigibberellin plant growth regulators (PGRs) may slow stem elongation and thus reduce maintenance costs in this environment. In Expt. 1, two PGRs were applied as foliar spray or drench to three spiderwort selections [two of zebra plant (Tradescantia zebrina) and one of inch plant (Tradescantia fluminensis)] immediately before installation in a green wall, each at three rates: ancymidol (ANC) foliar spray at 25, 100, and 200 mg·L−1; paclobutrazol (PBZ) foliar spray at 20, 80, and 160 mg·L−1; and PBZ drench at 1, 4, and 8 mg·L−1, along with an untreated control. In Expt. 2, 80 mg·L−1 PBZ foliar spray, 1 mg·L−1 PBZ applied via subirrigation four times, and the combination of these two treatments, was evaluated on ‘Burgundy’ zebra plant. In both experiments, plants were placed in a vertical modular tray interior green wall. Change in total stem and specific internode length were measured every 14 days after installation for 3 months to calculate growth per month. Antigibberellin application slowed internode elongation of spiderwort selections during the first month after installation. Antigibberellins were more effective in zebra plant at reducing overall stem growth rate and less so on inch plant. Across the three spiderwort selections, 25 mg·L−1 foliar spray of ANC resulted in no difference in growth rate when compared with the control, although 100 to 200 mg·L−1 foliar spray was effective. Based on the results of both experiments, moderate and high rates of PBZ, applied both as a foliar spray and drench, resulted in similar reduction in stem elongation. PBZ applied as 20 to 80 mg·L−1 foliar spray, 4 mg·L−1 drench before installation in the wall, or a combination of an 80 mg·L−1 PBZ pre-installation foliar spray and recurring 1 mg·L−1 via subirrigation (four times) were effective at growth suppression of spiderworts for at least 3 months. Even rates of PBZ of 160 mg·L−1 foliar spray or 8 mg·L−1 drench did not show phytotoxicity in treated plants and could be considered for use. We recommend a pre-installation application of 80 mg·L−1 foliar spray or 4 mg·L−1 drench for controlling stem growth across spiderwort selections. Application of antigibberellin PGRs to plants before installation in green walls slows stem growth and can contribute to reduced maintenance costs.